KEDUDUKAN HUKUM MENKOMINFO DALAM PELAKASANAAN PERDAMAIAN MENURUT UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Shabrina Aliya Pramudita; Kartikasari Kartikasari; Amelia Cahyadini (Legal Standing : Jurnal Ilmu Hukum, 2020)
Susension of Payment (PKPU) is the time given by the law through the commercial court’s judgment where the Creditor and the Debtor are given the chance to discuss the ways to pay their debts by giving the payment plan as a whole or in partial, including if it is considered necessary to restructure the debts. It is known that there is the implementation of the peace agreement in PKPU. The parties in the implementation of the peace agreement are the Creditor and the Debtor. Moreover, it is also known that there are Preferred Creditor and Concurrent Creditor. However, in regard to the classification of the Creditors, there are several cases that show that the Creditor’s legal standing is debatable and it creates a problem during the implementation of the peace agreement in PKPU.